PENGEMBANGAN BAHAN AJAR DIGITAL TERINTEGRASI EDUCATION FOR SUSTUINABLE DEVELOPMENT PADA MATERI ENERGI TERBARUKAN UNTUK MEMFASILITASI KEMAMPUAN BERPIKIR KRITIS SISWA - Badiah, Siti; Saefullah, Asep; Antarnusa, Ganesha (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research is motivated by Indonesia's impending energy crisis, where education is seen as one of the solutions to achieve sustainable development in the energy field. Therefore, there is a need for the concept or use of integrated Education for Sustainable Development (ESD) digital teaching materials in the physics subject on the topic of renewable energy. The research aims to determine the process of developing integrated ESD digital teaching materials, to assess the validation results of content and media experts on the teaching materials, and to understand students' responses to the acceptance of the teaching materials. The research method used is Research and Development (R&D) with the Thiagarajan 4-D research model modified with the define, design, and development stages. This study has developed integrated ESD digital teaching materials on renewable energy topics to facilitate students' critical thinking abilities in digital form through the assistance of the fliphtml5 website, which is categorized as very suitable. The expert validation results for content yielded a percentage of 87.6%, which was categorized as very suitable; the expert validation results for media yielded a percentage of 84.6%, which was also categorized as very suitable. Students' responses to accepting the teaching materials were 87.8%, categorized as very suitable.